AMPA receptors and perampanel behind selected epilepsies: current evidence and future perspectives. (2nd November 2017) - Di Bonaventura, Carlo; Labate, Angelo; Maschio, Marta; Meletti, Stefano; Russo, Emilio
ABSTRACT: Introduction : The alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptors are the major mediators of glutamate-mediated excitatory neurotransmission, and are critical for synchronization and spread of epileptic activity. Areas covered : AMPA receptor antagonists have been also developed as antiepileptic drugs and perampanel (PER) is the first highly selective, non-competitive AMPA-type glutamate receptor antagonist that is available on the market. It is approved as adjunctive therapy for the treatment of partial-onset seizures with or without secondary generalization, and for primary generalized tonic-clonic seizures in idiopathic generalized epilepsy, in patients aged ≥ 12 years. This article reviews the role of AMPA receptors in the neuronal hyperexcitability underlying epilepsy, the mechanism of action and clinical experience on the anti-seizure activity of PER. Moreover, the rationale for targeting AMPA receptor in specific epileptic disorders, including brain tumor-related epilepsy, mesial temporal lobe epilepsy with/without hippocampal sclerosis, and status epilepticus is evaluated. Finally, the pharmacological rationale for the development of AMPA receptor antagonists in other neurological disorders beyond epilepsy is considered. Expert opinion : Further research aimed at better understanding the pharmacology and blocking mechanism of PER and other AMPA receptor antagonists will drive future development of therapeutic agents that target epilepsy and other neurological diseases.